Therapeutic Role of Coenzyme Q10 in Brain Injury during Experimental Diabetes - Jihan Hussein, Dina Abo El-matty, Zakaria El-Khayat and Yasmin Abdel-Latif (Journal of Applied Pharmaceutical Science, 2013)
Diabetes mellitus is a complex disease associated with peripheral and central complications; these complications include retinopathy, nephropathy and neuropathy. Antioxidant therapies may be useful in decreasing the risk of diabetic complications. This study carried out to investigate the role of coenzyme Q10 (CoQ10) in decreasing oxidative stress as well as attenuating brain injury in diabetic rats. Sixty male albino rats were used in this study and classified into four groups (fifteen rats in each group) including; control, CoQ10, diabetic and treated groups. Fasting blood sugar was determined. Brain malondialdehyde (MDA), advanced oxidation protein products (AOPP), nitric oxide (NO) and superoxide dismutase (SOD) were estimated by colorimetric methods. In addition brain CoQ10 was estimated by HPLC method using C18 column and UV detector at 275 nm. Brain oxidant parameters were significantly increased in diabetic group concomitant with a reduction in brain antioxidants, while CoQ10 supplementation in treated group attenuated them. We concluded that oral CoQ10 may be a viable antioxidant strategy for neurodegenerative disease in diabetes mellitus.
Keywords: Diabetes mellitus, coenzyme Q10, HPLC, oxidative str